2019
DOI: 10.1039/c9ra08847d
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring glycosidase activity for clustered sugar substrates, a study on β-glucuronidase

Abstract: Enzymatically-triggered probes to determine glucuronidase hydrolysis kinetics for clustered substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The increasing awareness of the multilateral character of (hetero)multivalency, with additional reports expanding the range of MEI responsive glycosidases 235,236 and extending the generalized multivalent effect to the glycosyltransferase enzyme category [237][238][239] and anti-carbohydrate antigen antibodies, 240 will likely fuel research in carbohydrate supramolecular chemistry with a new perspective. The current embodiments exploiting the heteromultivalent effect to reach optimal cell targeting in vivo 76 and multivalent inhibitors to regulate the activity of diseaseassociated enzymes, e.g.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The increasing awareness of the multilateral character of (hetero)multivalency, with additional reports expanding the range of MEI responsive glycosidases 235,236 and extending the generalized multivalent effect to the glycosyltransferase enzyme category [237][238][239] and anti-carbohydrate antigen antibodies, 240 will likely fuel research in carbohydrate supramolecular chemistry with a new perspective. The current embodiments exploiting the heteromultivalent effect to reach optimal cell targeting in vivo 76 and multivalent inhibitors to regulate the activity of diseaseassociated enzymes, e.g.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…FimH LEctPROFILE kit assays from GLYcoDiag (Orléans, France) were performed according to GlycoDiag’s protocol already described [ 60 , 61 , 62 ]. Briefly, the interaction profiles of each compound were determined through a competitive inhibition assay based on the inhibition by the compounds of the interaction between FimH lectin coated onto the microplate surface and a biotinylated neoglycoprotein NeoM (Man-BSA) as a tracer.…”
Section: Methodsmentioning
confidence: 99%
“…β-Glucuronidase (GLU), lysosomal glycosidase, is an important biologically active protease that exists in the human body. GLU is mainly involved in the degradation of glycosaminoglycans containing glucuronides and is related to a variety of pathophysiological conditions in the organism. , In addition, GLU is also a tumor biomarker, and the active expression of GLU is closely related to tumor cell invasion, apoptosis, metastasis, and proliferation. Studies have shown that, compared with normal liver cells when liver cells become cancerous, the activity of GLU in liver tissues is significantly enhanced. In the normal liver detoxification process, toxic substances are combined with glucuronides under the action of uridine 5′-diphospho-glucuronosyltransferase to form hydrophilic substances that are eliminated from the body. In contrast, in cancerous liver cells, the overexpression of GLU will cause glucuronides to be overly decomposed and lose their ability to bind to harmful substances. , In the end, it is difficult for the organism to exclude the hydrophobic harmful substances from the body and the long-term accumulation of toxic substances in the organism results in the body’s pathological changes. ,, This is also an important reason why GLU has become a target for real-time monitoring and the early diagnosis of liver cancer. Therefore, developing a method to accurately detect and analyze GLU is the problem that researchers must solve.…”
Section: Introductionmentioning
confidence: 99%